2020
DOI: 10.1038/s41375-020-0756-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrated safety profile of selinexor in multiple myeloma: experience from 437 patients enrolled in clinical trials

Abstract: Selinexor is an oral, small molecule inhibitor of the nuclear export protein exportin 1 with demonstrated activity in hematologic and solid malignancies. Side effects associated with selinexor include nausea, vomiting, fatigue, diarrhea, decreased appetite, weight loss, thrombocytopenia, neutropenia, and hyponatremia. We reviewed 437 patients with multiple myeloma treated with selinexor and assessed the kinetics of adverse events and impact of supportive care measures. Selinexor reduced both platelets and neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 34 publications
0
60
0
Order By: Relevance
“…Selinexor has been tested in many types of cancers, with promising results in some [ 168 ]. To date, it is approved by the US Food and Drug Administration for the treatment of relapsed or refractory multiple myeloma [ 170 , 171 , 172 ].…”
Section: Targeting Crm1 In Cancermentioning
confidence: 99%
“…Selinexor has been tested in many types of cancers, with promising results in some [ 168 ]. To date, it is approved by the US Food and Drug Administration for the treatment of relapsed or refractory multiple myeloma [ 170 , 171 , 172 ].…”
Section: Targeting Crm1 In Cancermentioning
confidence: 99%
“…The present study was designed to determine the RP2D and assess The safety profile of SDd was similar to that observed with selinexor along with a low rate of IRRs and cytopenias from daratumumab. [34]. Rates of grade ≥3 neutropenia on SDd were considerably lower than those on daratumumab-IMiD combinations, and febrile neutropenia was not observed.…”
Section: Discussionmentioning
confidence: 91%
“…The starting dose was <60mg/dose for 21% of the patients, 61-80 mg/dose for 51%, 81-100 mg for 25% of the patients and >100mg for 3% of the patients (median weekly dose of 100 mg). 49 The most common hematologic AE was thrombocytopenia, and it was observed in 66% of all patients (any grade), whereas it was grade 3 in 22% of them and grade 4 in 32%. The experts suggest that the platelet count should be checked weekly in order to monitor potential thrombocytopenia, whereas twice weekly monitoring is advised for grade 3 thrombocytopenia.…”
Section: Management Of Toxicitiesmentioning
confidence: 94%
“…Pseudohyponatremia could not be ruled out due high paraprotein levels and hyperglycemia. 45,49 In the STORM trial, an assessment of the quality of life (QoL) of the patients showed a possible worsening in physical well being and functional well-being; however, it can not be exclusively attributed to the drug regimen, taking into consideration that the trial included heavily pretreated patients with RRMM. Future trials should carefully assess QoL-related indices using validated instruments of patients reported outcomes.…”
Section: Management Of Toxicitiesmentioning
confidence: 99%